High Temperature Oxidation Behavior of Nano-Alumina–Modified NiAl Coating - Fang, Yuqing; Shu, Xiaoyong; Dong, Shuhe (Frontiers in Materials, 2022)
In this paper, the nickel aluminide coating prepared by the chemical vapor deposition method has adhered deliberately with nano-alumina film on the surface by the electrophoresis method. The analysis results of oxidation behavior in the air at 1000 °C was reported that the nano-alumina particles adhered to nickel aluminide coating surface appear to be effective in facilitating the θ-Al2O3 to α-Al2O3 phase transformation. The fast θ to α phase transformation helps reduce the oxidation rate of the nickel-aluminum coating and prevents the cracking and peeling in the oxide scale. The research addressed a novel method to improve the high-temperature oxidation resistance of nickel aluminide coatings.